2017
DOI: 10.5114/pjp.2017.67583
|View full text |Cite
|
Sign up to set email alerts
|

Expression of resistin in the liver of patients with non-alcoholic fatty liver disease

Abstract: Adipokines are cytokines that presumably connect the pathologies of metabolic syndrome. One of the adipokines is resistin, the role of which in insulin resistance, obesity, and non-alcoholic fatty liver disease (NAFLD) needs to be determined. Liver biopsy specimens were obtained intraoperatively from 214 obese patients. Histological assessment was based on NAFLD activity score according to Kleiner. Statistical analysis involved semi-quantitive immunohistochemistry assessment of resistin staining and: NAFLD sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Furthermore, there is some evidence that Kupffer cells and infiltrating macrophages in steatotic livers might also contribute to the whole body production of the adipokine resistin and thereby enhance hepatic insulin resistance [ 148 ].…”
Section: Role Of Macrophages In the Development Of Insulin Resistance...mentioning
confidence: 99%
“…Furthermore, there is some evidence that Kupffer cells and infiltrating macrophages in steatotic livers might also contribute to the whole body production of the adipokine resistin and thereby enhance hepatic insulin resistance [ 148 ].…”
Section: Role Of Macrophages In the Development Of Insulin Resistance...mentioning
confidence: 99%
“…Resistin expression was increased in subjects with central obesity, T2D and NAFLD (19, 20). Although studies in animal models consistently show that resistin promotes insulin resistance, evidence for this effect in humans is unclear.…”
Section: Resistinmentioning
confidence: 99%
“…In another study by Tsochatzis [41] the level of resistin was found to be related to the severity of fibrosis. In the study conducted by Pagano [59] the level of resistin was found higher in patients with NAFLD compared to the control group, and a positive correlation with inflammation was found.…”
Section: Discussionmentioning
confidence: 85%